Association between low levels of physical fitness and sociodemographic factors in adolescents from rural and urban areas - Edio Luiz Petroski; Adelson Fernandes da Silva; Adriana Bispo Rodrigues; Andreia Pelegrini (Desafio Singular, 2012)
The objective was to evaluate the association between low levels of physical fitness and sociodemographic factors in adolescents from rural and urban areas. A cross-sectional study was conducted on 627 adolescents (299 from urban areas and 328 from rural areas) aged 14 to 17 years, who attended state public schools. Sociodemographic data, anthropometric measures and health-related physical fitness data (Physical Best) were collected. With respect to flexibility, adolescents from urban areas presented a 56% higher chance of inadequate flexibility than schoolchildren from rural areas. In the sit-up test, adolescents from rural areas presented an almost 10 times higher chance of inadequate muscle strength/endurance than those from urban areas. Regarding cardiorespiratory fitness, adolescents from urban areas showed a 91% higher chance of inadequate fitness than those from rural areas. In conclusion, adolescents from urban areas attending state public schools are more prone to inadequate health-related physical fitness than adolescents from rural areas.